LIMP Score and Anterior Cruciate Ligament Injury in Patient Undergoing Arthoscopy for Acute Knee Injury: An Observational Study - Mahesh Karmacharya; Binod Sherchan; Bikash KC; Ram Sharma Subedi; Badri Rijal; Saphalata Devi Koju (Journal of Nepal Medical Association)
Introduction: Globally, anterior cruciate ligament injury is common but difficult clinical diagnosis in acute setting because of pain during examination and difficult availability of investigations and diagnostic arthroscopy. Legs giving way, Inability to continue the task, Massive effusion and pop sound heard at the time of injury or LIMP score is a history based scoring which can be aid to diagnose anterior cruciate ligament injury. This study is designed to find out the proportion of patient with LIMP score of >2 having anterior cruciate ligament injury. Methods: An observational cross-section study was done among the patients visiting emergencies and out patient department of respective hospitals after approval from Institutional review Committee (Reference number: 23/2078/79). The LIMP score was assessed during the presentation and patients were followed up at arthoscopy for the final diagnosis. Results: There were 126 patients enrolled in the study among which 68 (54%) had LIMP score of >2. Out of the total, 74 (59%) had anterior cruciate ligament inury among which 67 (90.5%) had LIMP score >2. Among the patient who did not have anterior cruciate ligament injury, 51 (98%) had LIMP score <2. Conclusions: The proportion of patients having anterior cruciate ligament injury were higher in the category with LIMP score >2.